Public health and clinical approach to proactive management of frailty in multidimensional arena - Roller-Wirnsberger, R.; Liotta, G.; Lindner, S.; Iaccarino, G.; De Luca, V.; Geurden, B.; Maggio, M.; Longobucco, Y.; Vollenbroek-Hutten, M.; Cano, A.; Carriazo, A. M.; Goossens, E.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Demographic changes have forced communities and people themselves to reshape ageing concepts and approaches and try to develop actions towards active and healthy ageing. In this context, the European Commission launched different private-public partnerships to develop new solutions and answers on questions related to this topic. The European Innovation Partnership on Active and Healthy Ageing, including topic related action groups as well reference sites committed towards a common action to facilitate active and healthy ageing, has contributed key elements for interventions, scaled up best practices and evaluated impact of their action to drive innovation across many regions in Europe over the past years. Methods. This paper describes action taken by A3 action group in the European Innovation Partnership on Active and Healthy Ageing. This paper gives an overview of how the partnership combined the view on frailty coming from public health as well as the clinical management. Results. Within different European regions, to tackle frailty, EIPonAHA partners have conceptualized functional decline and frailty, making use of good practice models working well on community programs. The A3 Group of EIPonAHA has worked alongside a process of innovation, targeting all ageing citizens with the clear goal of involving communities in the preventive approach. Conclusion. Engagement needs of older people with a focus on functionally rather than disease management as primary objective is considered as an overarching concept, also embracing adherence, compliance, empowerment, health literacy, shared decision-making, and activation. Furthermore, training of staff working with ageing people across all sectors needs to be implemented and evaluated in future studies